The potential of labor training in primary school for formation pupils’ cross-cultural outlook and national self-conscious - Chernaya, Viktoria; Strukova, Svetlana (Lviv Polytechnic Publishing House, 2016)
The authors considers the role of labor education as factor of child holistic personality development, particularly the education of its communicative abilities, cross-cultural outlook and national self-conscious. There were analyzed the software and teaching material on labor education in primary school and revealed that the characteristics of the school subject in all educational related purposes.
Keywords: labor education; comprehensive personality development; content learning; intercultural potential; educational purpose